Heat recovery steam generator (HRSG) three-element drum level control utilizing Fractional order PID and fuzzy controllers. (March 2022) - Elhosseini, Mostafa A.; El-din, Ahmed shams; Ali, Hesham Arafat; Abraham, Ajith
Abstract: Shrink and swell is a phenomenon that causes transient variability in water level once boiler load variation occurs. The leading cause of the swell effect is the steam demand changes and the actual arrangement of steam generating tubes in the boiler. Steam bubbles beneath HRSG drum water make the level control very difficult, particularly with significant disturbances in the input heat to HRSG. Plant shutdown may occur in some situations, and combined cycle plant efficiency is diminished. The recently applied control methods in industry are single-element and three-element control with PID controllers, but these methods are not well suited for substantial load changes. The main aim of this paper is to investigate the shrink and swell phenomenon inside HRSG power plants. In addition to the existing PID loops, two different standalone controllers, namely, the FOPID controller and fuzzy controller, are implemented with the HRSG model. Besides, Artificial Bee Colony (ABC) algorithm is used to tune FOPID efficiently. Based on overshoot, rise time, ISE, IAE, ITAE as performance measures, the comparison has been held between the three controllers. Simulations show that how the ABC optimization algorithm is efficient with PID, FOPID. It turns out that the proposed method is capable of improving system responses compared to the conventional optimal controller. Highlights: Discussing the shrink/swell phenomenon of drum level. Discover how optimization algorithms can enhance PID controller response — By tuning it with the ABC algorithm. Presenting two new recent three-element controllers using FOPID and fuzzy logic. The application of ABC optimization algorithm to set the Membership function (MF) parameter of Fuzzy Logic. Conducting comparative analysis between PID, FOPID and the Fuzzy logic controllers.